Expanding depth and meaning within urban design processes through the application of complexity and evolutionary theories - Miguel, Marta; Laing, Richard; Leon, Marianthi; Baxter, Seaton (Journal of Architecture and Urbanism, 2021)
Previous research has established the value of regarding cities as complex systems, and as systems which will evolve over time. The research reported in this paper concerns the development of an approach to urban design and management which recognises the complexities of change resulting from design-led urban interventions. The research commenced with a study of urban design and urban management processes, and the manner in which they have been studied in an academic context. The system aims to guide the processes of urban design so that it can be implemented within a cyclical process of evaluation and application. The system aids communication across design teams and improves clarity within the design process for the designers themselves. The specific system also aspires to interconnect theory with practice, while supporting designers to be inclusive and holistic. The paper describes a case study where the framework was applied within an academic setting, related to real urban environments in Singapore. It validates the model’s ability to guide students through the design process, give depth to their analysis of urban systems and meaning to their designs. Action research was implemented, to reflect the need for a “practice-changing practice” methodology, that supports a greater understanding of the relationship between theory and practice.